Interacción Por Sexo Y Consumo De Alcohol En El Nivel De Celos E Infidelidad De Estudiantes De Licenciatura De La UAEH - Ostria, Alexia; Addauto, Lorena; Del Castillo, Arturo; Palencia, Angélica Romero (European Scientific Journal, ESJ, 2017)
The gradual increase of alcohol consumption in college students has become a public health problem at global and national level. Among the psychosocial consequences of this consumption is an increase in violence levels in dating relationships, mediated by factors such as jealousy and infidelity. Objective: to determine the interaction by sex and level of risk in alcohol consumption levels on jealousy and infidelity levels in college students. Material and Methods: 131 students were selected a nonprobabilistic convenience sampling. The age was from 17 to 23, M= 19.81, SD=1.89. 61.1% were women and 38.9% men. The Questionnaire Disorders Identification due to Alcohol Consumption (AUDIT), Multidimensional Inventory Jealousy (EMUCE) and Inventory Multidimensional Infidelity (IMIN) were used. They were conducted descriptive analyzes and factorial ANOVA 2x2. Results: Of the factorial ANOVA, indicate that women are more likely to feel greater levels of jealousy, while there is no difference between the level of infidelity in men and women. Conclusion: There are differences in sexuality as a reason for infidelity, saying that men without risk in consumption have lower levels in this factor than average risk women